2021
DOI: 10.3390/ijerph18041463
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effects of Fine Particulate Matter and Temperature on Preterm Birth in Seoul, 2010–2016

Abstract: Background: Preterm birth contributes to the morbidity and mortality of newborns and infants. Recent studies have shown that maternal exposure to particulate matter and extreme temperatures results in immune dysfunction, which can induce preterm birth. This study aimed to evaluate the association between fine particulate matter (PM2.5) exposure, temperature, and preterm birth in Seoul, Republic of Korea. Methods: We used 2010–2016 birth data from Seoul, obtained from the Korea National Statistical Office Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
(34 reference statements)
0
8
0
1
Order By: Relevance
“…Similar risk was also found for a subpopulation with low average ambient temperature (≤−0.59°C) in the third trimester, 60 highlighting that both extremes of temperature may be cause for concern. Several other studies conducted in Asia have corroborated this newly identified potential for synergistic risk 61,62 …”
Section: Climate Change and Reproductive Health Outcomesmentioning
confidence: 53%
See 1 more Smart Citation
“…Similar risk was also found for a subpopulation with low average ambient temperature (≤−0.59°C) in the third trimester, 60 highlighting that both extremes of temperature may be cause for concern. Several other studies conducted in Asia have corroborated this newly identified potential for synergistic risk 61,62 …”
Section: Climate Change and Reproductive Health Outcomesmentioning
confidence: 53%
“…Several other studies conducted in Asia have corroborated this newly identified potential for synergistic risk. 61 , 62 …”
Section: Climate Change and Reproductive Health Outcomesmentioning
confidence: 99%
“…Several studies have reported that exposure to high-temperature changes increases the risk of premature birth. 26 , 38 Heat stress could activate the fetal hypothalamic-pituitary-adrenal axis, prompting the placental release of estriol, prostaglandins which could induce labor onset. 38 …”
Section: Discussionmentioning
confidence: 99%
“…However, exposure to combined effects of temperature and air pollutants on birth outcomes has been scarcely studied. 26 , 27 Wang et al 27 evaluated heatwaves on PTB and reported synergistic effects of PM 2.5 and heat waves, with more PTB with a combination of high PM 2.5 and heatwaves in the week before birth. Kwag et al, 26 in contrast, found that PM 2.5 exposure during the first trimester (TR1) increased the risk of preterm birth among pregnant women exposed to low temperatures during TR1.…”
Section: Introductionmentioning
confidence: 99%
“…Still, thus far, the results of studies on the effects of maternal exposure during pregnancy have been inconsistent. The sensitive window of exposure and the influence level of air pollutants have varied greatly [ 6 , 7 , 8 ]. Further, some of the studies are ecological in nature or limited by a small sample size [ 9 ].…”
Section: Introductionmentioning
confidence: 99%